URBAN CLIMATE CHANGE IN CENTRAL AREA OF SAO PAULO USING HIGH RESOLUTION SATELLITE IMAGERY - Lombardo, Magda Adelaide; Freitas, Monica Kofler [UNESP]; Misra, S. C.; Revetria, R.; Sztandera, L. M.; Iliescu, M.; Zaharim, A.; Parsiani, H. (World Scientific And Engineering Acad And Soc, 2008)
Current urban conditions in central metropolitan areas demand emergency actions involving implementation of public policies and directives to minimize heat islands. Heat islands produce thermal stress and are harmful to public health, and can be intensified by the lack of adequate planning regarding public spaces. Based on analyses carried out with the application of GIS, the present study verified the distribution of urban vegetative cover and land use types using a mosaic of high resolution satellite images (IKONOS II, 2002) and ETM+/LANDSAT-7 thermal images from 1999 to 2004 in the central districts of the city of Sao Paulo. Although studies have already shown that vegetative cover can minimize heat island, reducing public health risks and energy consumption resulting from air conditioning, such transformations demand strategic actions and the application of specific instruments of urban regulation aiming to establish environmental quality.
Keywords: Urban Climate Change; Sao Paulo; High Resolution Satellite Imagery